Volume 2: Turbo Expo 2007 2007
DOI: 10.1115/gt2007-27687
|View full text |Cite
|
Sign up to set email alerts
|

Micro Gas Turbine Combustor Emissions Evaluation Using the Chemical Reactor Modelling Approach

Abstract: Chemical Reactor Modelling approach has been applied to evaluate exhaust emissions of the newly designed ARI100 (Patent Pending) recuperated micro gas turbine combustor developed by Ansaldo Ricerche SpA. The development of the chemical reactor network has been performed based on CFD reacting flow analysis, obtained with a global 2-step reaction mechanism, applying boundary conditions concerning the combustion chamber at atmospheric pressure, with 100% of thermal load and fuelled with natural gas. The network c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…21,22 Russo built a reaction network model based on the CFD reaction flow analysis of small gas turbines to study the CO and NOx emissions of different fuels. 23 The results were in good agreement with the experimental results under typical operating conditions. Lebedev et al established a simple reaction model based on CFD simulations using different mechanisms for methane and kerosene.…”
Section: Introductionsupporting
confidence: 84%
“…21,22 Russo built a reaction network model based on the CFD reaction flow analysis of small gas turbines to study the CO and NOx emissions of different fuels. 23 The results were in good agreement with the experimental results under typical operating conditions. Lebedev et al established a simple reaction model based on CFD simulations using different mechanisms for methane and kerosene.…”
Section: Introductionsupporting
confidence: 84%
“…The EDM model assumes that chemical reaction rates are higher than turbulent mixing. This model is useful in the simulation of all types of combustion systems (turbulent premixed and non-premixed combustion), mainly when it includes a fuel with a high reaction rate (Fichet et al, 2010;Hao, 2014;Kanniche, 2010;Russo et al, 2007;Frassoldati et al, 2009;Bulat et al, 2014). In this model, the fast reaction rates are controlled by the turbulent mixing rate, the kinetics usually defined by one-or two-step mechanisms and nonequilibrium is not considered.…”
Section: Ransmentioning
confidence: 99%
“…Researchers have long established that an Equivalent Reactor Network (ERN) can represent a reacting flowfield in a cost-effective and accurate way to account for detailed kinetics and to predict the behavior of a combustor or chemical process, including trace-species emissions. Gas-turbine manufacturers, for example, routinely use perfectly-stirred-reactor (PSR) and plug-flow-reactor (PFR) networks to model gas-turbine combustor behavior, particularly for predictions of CO and NOx emission levels, where detailed kinetics are required [6][7][8]. Kendrick, and coworkers at UTRC [6], for example, showed that networks of perfectly stirred reactors (PSRs) with detailed chemistry can accurately simulate an industrial combustor.…”
Section: Reactor Network and Energico® Softwarementioning
confidence: 99%